Acid-base regulation and other metabolic changes during an 800m running: A study in competitive runners - Yates, K.; Weston, A. R.; Graham, K. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
It has been shown from post race investigations that the 800m running event causes marked disturbances to metabolic homeostasis. However there is little data on the time course of changes during the race. This investigation examines the changes that occur both during an 800m time trial and across a season of training. Nine competitive middle distance runners participated in the study: (mean ± SD) height=174 ± 7.2 cm, weight=66.6 ± 10.6 kg. Subjects were tested in two blocks, 6 months apart. Each test block consisted of an 800m maximal effort time trial followed by, on separate days and in randomised order, a 400m and 600m run based on paces determined from the 800m split times. Arterialised capillary blood samples were drawn pre (rest) and 30 second post-exercise and analysed for pH, pCO2, lactate, potassium (K+) and sodium (Na+). Bicarbonate (HCO3-) concentration and buffering capacity (BC) were calculated from measured values. (expressed as mmol/l increase in lactate that results in a one unit change in pH). Pre vs post training data were analysed for 5 of the 9 subjects. Pre training data showed significant (p<0.001) changes with increasing distance (rest, 400, 600 and 800m) for lactate (2.6 ± 0.7, 11.1 ± 11.1, 11.9 ± 0.6, 14.5 ± 2.3 mmol.l-1), pH (7.41 ± 0.03, 7.24 ± 0.05, 7.16 ± 0.06, 7.12 ± 0.08), HCO3- (24.2 ± 1.5, 16.0 ± 1.8, 12.2 ± 2.3, 9.7 ± 2.0 mmol.l-1) with the majority of buffering occurring in the first 400m (rest - 400m, 55.5 ± 18.9; 400m - 600m, 11.6 ± 35.0; 600m - 800m, 23.3 ± 47.4, p<0.05). Significant changes were also seen with increasing distance (p<0.001) for K+ (5.03 ± 0.4, 6.4 ± 0.6, 6.0 ± 1.3, 5.5 ± 0.90 mmol.l-1) and Na+ (140.5 ± 1.3, 144.0 ± 4.2, 145.0 ± 3.1, 143.6 ± 4.3 mmol.l-1). Analysis of pre vs post training data showed a significantly lower accumulation of lactate post training (p<0.05) although differences in pH and buffering capacity failed to reach a significant level.